A Virtue-Ethics Analysis of Supply Chain Collaboration - Drake, Matthew J. (Journal of business ethics, 2008)
Technological advancements in information systems over the past few decades have enabled firms to work with the major suppliers and customers in their supply chain in order to improve the performance of the entire channel. Tremendous benefits for all parties can be realized by sharing information and coordinating operations to reduce inventory requirements, improve quality, and increase customer satisfaction; but the companies must collaborate effectively to bring these gains to fruition. We consider two alternative methods of managing these interfirm supply chain relationships in this article. The first, which we have named “dictatorial collaboration,” occurs when a dominant supply chain entity assumes control of the channel and forces the other firms to follow its edicts. We compare and contrast this method with “sustainable collaboration,” in which the parties share resources and engage in joint problem solving to improve the performance of the system as a whole. We use a virtue ethics lens to describe these methods of relationship management to suggest that sustainable collaboration is preferable to dictatorial collaboration both operationally and ethically in the long run.